2017
DOI: 10.3847/1538-4357/aa8b6c
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Virgo Cluster Survey. XXI. The Weak Lensing Masses of the CFHTLS and NGVS RedGOLD Galaxy Clusters and Calibration of the Optical Richness

Abstract: We measured stacked weak lensing cluster masses for a sample of 1323 galaxy clusters detected by the RedGOLD algorithm in the Canada-France-Hawaii Telescope Legacy Survey W1 and the Next Generation Virgo Cluster Survey at 0.2 < z < 0.5, in the optical richness range 10 < λ < 70. This is the most comprehensive lensing study of a ∼ 100% complete and ∼ 80% pure optical cluster catalog in this redshift range. We test different mass models, and our final model includes a basic halo model with a Navarro Frenk and Wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 124 publications
1
7
0
1
Order By: Relevance
“…This value is consistent within 1σ with previous analyses performed on CMB weak lensing (Melin & Bartlett 2015), and gives slightly higher results than previous galaxy-galaxy weak-lensing based analyses, but the results are still consistent (see e.g. Medezinski et al 2018;Sereno et al 2017;Jimeno et al 2017;Parroni et al 2017;Battaglia et al 2016;Applegate et al 2016;Smith et al 2016;Hoekstra et al 2015;Simet et al 2015;Israel et al 2015;von der Linden et al 2014;Donahue et al 2014;Gruen et al 2014;Mahdavi et al 2013. This value for b is also consistent with previous results obtained from the tSZ analysis performed in Hurier & Lacasa (2017), but it favours slightly lower values than the combined analysis of CMB and tSZ performed by Salvati et al (2017).…”
Section: Measurement Of the Hydrostatic Mass Biassupporting
confidence: 81%
See 1 more Smart Citation
“…This value is consistent within 1σ with previous analyses performed on CMB weak lensing (Melin & Bartlett 2015), and gives slightly higher results than previous galaxy-galaxy weak-lensing based analyses, but the results are still consistent (see e.g. Medezinski et al 2018;Sereno et al 2017;Jimeno et al 2017;Parroni et al 2017;Battaglia et al 2016;Applegate et al 2016;Smith et al 2016;Hoekstra et al 2015;Simet et al 2015;Israel et al 2015;von der Linden et al 2014;Donahue et al 2014;Gruen et al 2014;Mahdavi et al 2013. This value for b is also consistent with previous results obtained from the tSZ analysis performed in Hurier & Lacasa (2017), but it favours slightly lower values than the combined analysis of CMB and tSZ performed by Salvati et al (2017).…”
Section: Measurement Of the Hydrostatic Mass Biassupporting
confidence: 81%
“…Medezinski et al 2018;Sereno et al 2017;Jimeno et al 2017;Parroni et al 2017;Battaglia et al 2016;Applegate et al 2016;Smith et al 2016;Hoekstra et al 2015;Simet et al 2015;Israel et al 2015;von der Linden et al 2014;Donahue et al 2014;Gruen et al 2014;Mahdavi et al 2013). These studies, mostly relying on assumptions of unbiased weak-lensing mass estimates, obtained b 0.20 ± 0.08.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that WL reconstruction provides unbiased estimates of the true mass, many teams derived bias estimates (e.g. Medezinski et al 2018;Sereno et al 2017;Jimeno et al 2018;Parroni et al 2017;Battaglia et al 2016;Applegate et al 2016;Smith et al 2016;Hoekstra et al 2015;Simet et al 2015;Israel et al 2015;von der Linden et al 2014;Donahue et al 2014;Gruen et al 2014;Mahdavi et al 2013, shown as black dots, from top to bottom, in Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
“…The slopes we derived for the mass-amplitude relation (1.99± 0.10) and the mass-richness relation (1.71 ± 0.08) are significantly larger than typical results in literature about calibration of photometric observables. For example, the logarith- mic dependence of the weak lensing mass on the richness λ provided by redMaPPer has been found to be 1.12 ± 0.26 in Melchior et al (2017) and 1.33 +0.09 −0.10 by Simet et al (2017), while Parroni et al (2017) derived a slope 1.02 ± 0.21 for the calibration of RedGOLD λ. This likely depends on the fact that AMICO uses a fixed radius in the definition of its observables, as already discussed in Section 5.3 of Bellagamba et al (2018): clusters bigger than the model are cut by the kernel, smaller ones are slightly enhanced by correlated large-scale structure.…”
Section: Slope Of the Mass-observable Relationmentioning
confidence: 99%